(untitled) (Indonesian Journal of Education (INJOE), 2025)
This study is entitled “Strengthening Pancasila Character Through Integration of Human Values (Study of Mega Buana University Students)” and aims to examine how the humanitarian values in Pancasila are integrated into the lives of students and their impact on character formation. Pancasila, especially the second principle, emphasizes the importance of a just and civilized humanitarian attitude, but its implementation among students still faces challenges such as intolerance and individualism. Through a descriptive qualitative approach, this study collects data from in-depth interviews, observations, and documentation studies of Mega Buana University students. The results of the study indicate that students’ understanding of the values of humanity in Pancasila is still diverse, and its application in everyday life is influenced by social, educational, and campus cultural environmental factors. The integration of human values in academic and extracurricular activities has been shown to have a positive impact in shaping the character of students who are more caring, fair, and socially responsible. This study concludes that the integration of human values in the curriculum and campus activities needs to be improved to form a generation of students based on the values of Pancasila, especially in facing today’s social challenges.